1996
DOI: 10.1001/archneur.1996.00550030077025
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Subtypes and Hypertension

Abstract: In patients with stroke and hypertension, associated risk factors influence the subtype of stroke (hemorrhage vs brain ischemia, large- vs small-artery disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
1
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 30 publications
3
11
1
1
Order By: Relevance
“…Thus, DM is an equally important risk factor for both LVI and SVI, but has a discriminant impact on different vascular pathology: atherosclerosis/microatheroma versus fibrinoid degeneration of small vessels. Our data are consistent with previous studies which showed that DM did not differentiate LVI from SVI in stroke patients in general [11]or hypertensive stroke patients [2]. Other studies have also shown that DM is a risk factor for extracranial disease [12], intracranial disease [13, 14], lacunar infarction [15, 16], but not ICH [17].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, DM is an equally important risk factor for both LVI and SVI, but has a discriminant impact on different vascular pathology: atherosclerosis/microatheroma versus fibrinoid degeneration of small vessels. Our data are consistent with previous studies which showed that DM did not differentiate LVI from SVI in stroke patients in general [11]or hypertensive stroke patients [2]. Other studies have also shown that DM is a risk factor for extracranial disease [12], intracranial disease [13, 14], lacunar infarction [15, 16], but not ICH [17].…”
Section: Discussionsupporting
confidence: 92%
“…Perhaps, the dichotomized effect of serum cholesterol may be apparent only at its extreme level [31, 33]. Finally, the presence of history of ischemic heart disease has been shown to be a discriminant factor favoring proximal (vs. distal) vascular disease [2]. This was not confirmed by our results, which may be attributed to the very low prevalence of coronary heart disease in our study population (6%).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…1,4,5 Data for the UK black population are sparse, and characteristics such as risk factor profiles from one ethnic group may not be representative of another. 3 Studies that have examined cerebrovascular risk factor profiles have focused on comparisons between hemorrhagic and ischemic stroke, 6 categorizing ischemic stroke broadly into lacunar and nonlacunar infarct [7][8][9] or into etiologic subtypes. 10,11 A widely used classification system, the Bamford classification, 12 classifies cerebral infarction according to the vascular territory involved.…”
mentioning
confidence: 99%